Effect of Lactiplantibacillus plantarum LPJZ-658 on caecum microbiota and serum metabolomics of Luhua broiler - Li, Mengjiao; Liu, Zhongyuan; Chen, Chen; Liu, Ziqi; Liu, Liming (Frontiers in Microbiology, 2025)
IntroductionThe purpose of this study was to investigate the effects of dietary supplementation of Lactiplantibacillus plantarum LPJZ-658 on body weight and serum indexes of Luhua broiler, and to explore the relevant mechanism of probiotic function of LPJZ-658 based on intestinal microbiota and serum metabolomics.MethodsOne hundred one-day-old Luhua broiler were randomly divided into the control group (CON) and LPJZ-658 treatment group (LPJZ-658). The CON group was fed a basal diet, and the LPJZ-658 group was fed the basal diet supplemented with 2 × 109 cfu/kg of LPJZ-658. The study lasted for 28 days. At the end of the experiment, serum and caecum samples were collected for analysis.ResultsIn the LPJZ-658 group, the serum IgA level, and activity of SOD were significantly higher, concentration of MDA was markedly lower than in the CON group. Caecum microbiota showed that LPJZ-658 could dramatically change the composition of cecum flora. It’s mainly by increasing the level of Lactobacillus, Lachnoclostridium, and Parasutterella, and reducing the level of Clostridia_UCG-014, Faecalibacterium, Blautia, Eubacterium_coprostanoligenes_group, Anaerofilum and Shuttle. In addition, serum non-targeted metabolomics results showed that there were 49 serum differential metabolites between the two groups, and the main metabolic pathways affected by LPJZ-658 included phenylalanine, tyrosine and tryptophan biosynthesis, arachidonic acid metabolism, and tyrosine metabolism.DiscussionIn summary, LPJZ-658 can improve the serum immune performance and antioxidant capacity of Luhua broiler by regulating the composition of caecum microbiota and serum metabolome, thus improving the health status of Luhua broiler and culture efficiency.